Սահակ Պարթևի Հայրապետության շրջանը որպես հոգևոր վերածնության սկիզբ - Մելիքյան, Կարինե (ՀՀ ԳԱԱ Պատմության ինստիտուտ)
The period of Patriarchate of Sahak Partev was the start of spiritual regeneration. Just in this time for the following ages had become clear the dogmata, which is fallen in the basic of theology of the Armenian Church. Период патриаршества Саака Партева (387-436) стал началом духовного возрождения. Именно в этот отрезок времени для последующих веков более конкретизируется догматика, которая легла в основу богословского учения Армянской Церкви.
Keywords: Հայոց պատմություն; Քրիստոնեություն; Հայ եկեղեցու պատմություն; Հայ եկեղեցու գործիչներ